The origin of boulders in the Neoproterozoic of Eastern Sayan Ranges, south‐west Siberia: Glacial transport versus winnowed concretions. (10th April 2022) - Aleksandrov, Dmitrii
Abstract: The Cryogenian geological record of Siberia is scarce and ambiguous. Late Neoproterozoic strata of presumed glaciogenic origin of the Marnya Formation, Oselok Group cropping out along the Uda River in the Eastern Sayan Ranges, south‐western Siberia has received considerable attention due to the presence of at least three distinctive diamictite units. The lower diamictite unit (Karapchetui Member) is in subvertical contact (previously interpreted as a glacial valley) with stratigraphically older strata of the Tagul and Ipsit formations of the Karagas Group, and is represented by a wedge‐shaped unit of breccia that hosts numerous ellipsoidal sandstone bodies (previously thought to be boulders). The boulders are here reinterpreted as early diagenetic quartz and feldspar‐cemented sandstone concretions exhumed and redeposited from the Ipsit Formation when the latter was still uncemented and easily erodible. Tectonic compression, reverse faulting and localised continuous syndepositional uplift led to exhumation of the concretions, whereas subsequent extension, reactivation of the fault and 'negative inversion' of the basin produced accommodation space for redeposition of the exhumed concretions. In the process of redeposition, exfoliating concretions produced abundant debris that provided clasts for the breccia deposit. The Karapchetui diamictite, therefore, can serve as a sedimentary archive of late Neoproterozoic tectonic activity at the south‐western margin of the Siberian Craton. Abstract : In this study I demonstrate that Neoproterozoic diamictites long thought to be related to Snowball Earth glaciations could have a non‐glacial origin and represent a pile of exhumed and redeposited quartz‐cemented and feldspar‐cemented sandstone concretions. In addition to being essentially the first documented Proterozoic deposits consisting of exhumed and redeposited concretions, the results have wider implications casting some doubt upon the hypothesis of pervasive early diagenetic silicification during the Neoproterozoic, and suggesting a complicated tectonic evolution of the south‐western margin of Siberia inconsistent with the current view of Rodinia break‐up.